Professionalisation of Mathematics Teacher Educators: Methodology for a Case Study of a Higher Education Institution in Zambia (British Journal of Multidisciplinary and Advanced Studies, 2025)
Mathematics teacher educators (MTEs) engage in continuing professional development (CPD) through workshops, conferences, research collaborations, and educational technologies. However, research on the long-term impact and underlying processes of teachers’ participation remains limited. Additionally, long-term funded CPD opportunities are infrequent, often failing to address evolving technologies and specific needs. Continuing professional development efforts face challenges such as inadequate funding, limited research access, fewer opportunities, lack of initiatives, personal commitment issues and traditional methodologies. This paper explores the methodology from an interpretivist perspective in investigating the professionalisation of MTEs in the context of a longitudinal CPD.